Strategi Peningkatan Kinerja SDM di Waralaba “Kopi Titik Koma” The Hok Jambi - Anaseputri Jamira; Fachruddin Razi; Muhammad Amali; Yulita Febriani (Universitas Batanghari Jambi, 2023)
This study aims to formulate a strategy for improving the performance of Human Resources (HR) at The Hok Coffee Shop